Trees and vegetation on Pitka Divide, hills that run in a northwestern line from the foothills of the Terra Cotta Mountains, Alaska, August or September 1914 - University of Washington Libraries. Special Collections Division.
Caption under photo: Pitka Divide. McPherson number: K379 PH Coll 495.2-26a Photograph from album created in circa 1914 by James Lennox McPherson, a civil engineer, that documents the activities of the Kuskokwim Reconnaissance survey party (known as Party No. 11 of the Alaska Railroad Commission expedition). The A.E.C. had assigned McPherson to research the feasibility of building a branch railroad from Anchorage west to the mining districts on the Kuskokwim and Iditarod Rivers.